Analisis Deskriptif tentang Kesiapan Guru Mengajar dalam Penerapan Kurikulum Merdeka - Dahlia; D., Hamidah; Sitepu, Dewi Rulia (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to analyze the readiness of teachers in implementing the Independent Curriculum at Esa Perkasa Private High School. As a recently introduced national education policy, the Independent Curriculum emphasizes student-centered learning, character development, and pedagogical flexibility that allows teachers to design contextually relevant learning activities. This research employed a descriptive qualitative method, with data collected through interviews, classroom observations, and documentation studies. The research subjects consisted of teachers from various subject areas at the school. The findings indicate that most teachers possess a basic understanding of the principles and structure of the Independent Curriculum and have begun applying them in instructional practices. However, several challenges persist, including limited comprehensive training, inadequate school facilities to support differentiated learning, and difficulties in developing teaching modules and assessments aligned with curriculum guidelines. These obstacles influence the consistency and depth of curriculum implementation in daily teaching activities. Overall, teacher readiness can be categorized as fairly good, yet further institutional support, mentoring, and continuous professional development are required to ensure optimal and sustainable implementation of the Independent Curriculum.